Cellular, matrix, and mechano-biological differences in load-bearing versus positional tendons throughout development and aging: a narrative review. (3rd September 2018) - Choi, Rachel; Smith, Margaret; Clarke, Elizabeth; Little, Christopher
ABSTRACT: Purpose: Summarise available evidence comparing the cellular, biochemical, structural and biomechanical properties, and the changes that occur in these parameters in response to stimuli, in differentially loaded tendons across different stages of life. Methods: The PubMed database was searched for literature pertaining to differences between tendons using the term "tendon" or "tendinopathy", plus one or more of the following descriptors: "loading", "positional", "weight- or load-bearing", and "energy-storing". The abstracts were reviewed and relevant full-length articles retrieved and used to assemble a narrative review. Results: The incidence and prevalence of tendon disorders ("tendinopathies") is increasing in Western societies, with limited evidence that currently available treatments have any significant long-term effect on the disease course. A key emerging hypothesis is that disease in different tendons and even different regions within a tendon may be distinct. The available literature indicates that there are phenotypic differences, not only in the constitutive compositional and material properties but also in resident cells of positional compared with load-bearing tendons. Evident during early tendon growth, such differences have become well established by adulthood. Conclusions: The pheno-endotype of tendinopathy may be distinct between load-bearing tendons compared to positional tendons, which has translational implications with regard to preventing and managing tendinopathy. Better understanding of the molecular, cellular, and biomechanical pathophysiology underlying disease phenotypes, will allow more targeted/personalised treatment and therefore improve outcomes.